Translanguaging as a Pedagogical Strategy in Multilingual English Classrooms: A Qualitative Study from Indonesia - Ramadhan, Ridho; Kurnia, Yona; Safitri, Ririn (Jurnal Tahuri, 2022)
This study explores translanguaging practices as a pedagogical strategy in English language teaching within multilingual classrooms in Indonesia, focusing on public schools that reflect local linguistic diversity. In Indonesian English education, an “English-only” approach remains dominant despite students’ heterogeneous sociolinguistic realities. Conducted at SMP Negeri 5 Pekanbaru, Riau, where students use Minangkabau, Malay, and Indonesian in daily interaction, this qualitative case study collected data through four classroom observations, semi-structured interviews with one English teacher and twelve students, and document analysis of teaching materials and school policies. Thematic analysis was applied to identify patterns of translanguaging practices, students’ perceptions, and supporting and inhibiting factors. Findings reveal that translanguaging occurs in three structured and contextualized forms: (1) using local and national languages to mediate complex vocabulary and grammar concepts, (2) managing classroom instruction and discussions through combined use of Minangkabau, Malay, and Indonesian to ensure equitable understanding, and (3) linking local cultural examples to explain English idioms and expressions. Students responded positively, as these practices enhanced comprehension, linguistic inclusion, and participation. Key enablers included linguistic diversity as a learning resource, teacher flexibility, and cultural proximity; barriers included rigid “English-only” policies, limited teacher training, and conservative views toward local language use. The study’s novelty lies in documenting a tri-lingual classroom context (Minangkabau–Malay–Indonesian), expanding translanguaging research beyond typical bilingual settings. Conceptually and practically, this study contributes to education and applied linguistics by offering a context-responsive pedagogical model and advocating for more flexible language policies in Indonesian classrooms.